Small Clinic Electronic Health Records Implementations: An Options Thinking View - Helton, Joey; Wade, Dawn; Erhardt, Rich (Journal of Management Policy and Practice, 2017)
The rapid evolution of electronic health records (EHR) has made it difficult for small medical and dental practices to remain competitive. While studies have shown that offices who use EHR receive more insurance reimbursements, it is unclear how offices should choose the appropriate implementation. Research suggests that office decision makers can make better-informed decisions by examining real options. However, researchers have never evaluated real options in relation to implementation choices governed by federal regulations. To examine this gap in the literature, we address EHR software implementations using real options theory to determine how these options can best serve decision makers.